Friday

April 18, 2014

April 18, 2014

Posted by **Denise** on Wednesday, January 10, 2007 at 12:18am.

3 ln y= 1/2ln (2x+1) - 1/3ln (x+4) + ln C

ln y = (1/6)ln (2x+1) -(1/9)ln (x+4) + (1/3) ln C

y = e^ln y = e^[(1/6)ln (2x+1) -(1/9)ln (x+4) + (1/3) ln C]

= C^(1/3)* (2x+1)^(1/6) /(x+4)^(1/9)

**Related Questions**

integration by parts - s- integral s ln (2x+1)dx ? = ln(2x+1)x - s x d( ln (2x+1...

ALGEBRA - Contract the expressions. That is, use the properties of logarithms to...

Math differentiation - 1. y = x^x 2. y = (sin^2xtan^4x)/(x^2+1)^2 3. y = x^(1/x...

A big one! - Using logarithmic differentiate technique, find dy/dx y = [(x-3)³(x...

Math - ln x^2(x+1)/x+2 Write in terms of ln(x), ln(x+1), and ln(x+2) is the ...

Math - Find the derivative of: ln(2x/x+1) the answer is 1/x(x+1) but i can't ...

ALGEBRA - Contract the expressions. That is, use the properties of logarithms to...

Help, Math. - Solve: 3e2x + 2 = 50 a. ln 8 b. ln 0.25 c. ln 14 d. 0.5ln 16...

Math - exponential function - Find all real numbers that satisfy (6^x)(7^(2x...

Precalc - How to solve for x: 2^(2x) + 2^(x) -12 = 0 Steps too I tried solving ...